Application of SVD Method Using Magnetic Data to Identify Subsurface Structures at the Geothermal Area of Sonai Village and its Surroundings, Puriala, Konawe - Salmatia, Wa Ode; Manan, Abdul; Bahdad; Chahyani, Rani; La Ode Andimbara (ECOTAS, 2025)
This research was conducted with the aim of identiying the subsurface structures of the geothermal area of ??Sonai Village and its surroundings, Puriala, Konawe using the Second Vertical Derivative (SVD) method. The magnetic data used were obtained through measurements at 126 points. The total magnetic anomaly value obtained after Diurnal and IGRF corrections was -171.17 to 82.47 nT. After carrying out Upward Continuation and further processing, a residual magnetic field anomaly value of around -150 to 90 nT was obtained. Then the SVD method is applied to residual anomalous data that has been reduced to the Pole. Based on the SVD results and 2D modeling, several types of fault structures were found in the research area, consisting of 2 upward faults and 4 normal faults. The closest minor fault to the manifestation is at coordinates 4°1'16.41